New genus Arxellia with new species of Solariellidae (Gastropoda: Trochoidea) from New Caledonia, Papua New Guinea, Philippines, Western Australia, Vanuatu and Tonga - Vilvens, Claude; Williams, Suzanne T.; Herbert, David G. (Zootaxa, 2014)
A new genus, Arxellia, is described in the family Solariellidae. Nine species are referred to this taxon, eight of which are new and are described in this paper (Arxellia trochos n. sp., Arxellia boucheti n. sp., Arxellia herosae n. sp., Arxellia helicoides n. sp., Arxellia tracheia n. sp., Arxellia thaumasta n. sp., Arxellia maestratii n. sp. and Arxellia erythrea n. sp.). The previously described species Bathymophila tenorioi Poppe, Tagaro & Dekker, 2006 is reassigned to Arxellia.